Psychosocial implications of child sexual abuse on the nonoffending caregivers following the disclosure: A call for an extended support - Ramphabana, Livhuwani; Kgatla, Lesedi; Nxiweni, China (Technium Social Sciences Journal, 2022)
Child sexual abuse continues to be a threat to achieving healthy and socially desired development of children across the globe. It leaves unbearable impacts on the child victims. As much as child sexual abuse brings about severe impacts on children, it equally affects the surrounding support systems such as caregivers and families. Caregivers are of specific and unique characteristics to this paper. The authors' central argument is that providing support to non-offending caregivers may help victims adjust and heal from the abuse. This paper is aimed at identifying and describing the psychosocial implications of CSA on the non-offending caregivers – and bring forth the importance of supporting caregivers so that they can extend the necessary support to the child victims of sexual abuse. The authors reviewed and analysed literature in order to develop descriptive themes. The resilience theory was used as a guiding conceptual framework. Five themes were developed and discussed: psychological distress, fear and anxiety, shame in the context of family, lack of support from family, and balancing work and parenting. The paper concludes that in addition to focusing on the well-being of the victims, it is also imperative to focus on the support that the non-offending caregivers need as they are not exempted from experiencing psychosocial impacts following the disclosure of their children’s abuse. Recommendations for practice and research are also made.